2021
DOI: 10.3390/fi13100253
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Collaborative Virtual Conference Application: Challenges, Requirements and Guidelines

Abstract: Due to the recent COVID-19 pandemic that has swept the globe, more people are working from home. People use synchronous applications to communicate remotely because they are not able to meet face-to-face. However, few research studies on the issues surrounding the virtual conference application, particularly those that include collaborative activities, have been conducted. The usability study recruited 16 participants (in four groups of four) to communicate synchronously while performing collaborative activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Students in Song et al’s (2004) research encountered some additional technical problems like downloading errors, issues with installation, login problems with audio and video, etc. Ming et al (2021) found that some features like file sharing, whiteboard, and annotation are not easy to use, resulting in the underapplication of conferencing functions. It is worth making clear that teachers’ mastery of technology also affects students’ engagement ( Masry-Herzallh and Stavissky, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students in Song et al’s (2004) research encountered some additional technical problems like downloading errors, issues with installation, login problems with audio and video, etc. Ming et al (2021) found that some features like file sharing, whiteboard, and annotation are not easy to use, resulting in the underapplication of conferencing functions. It is worth making clear that teachers’ mastery of technology also affects students’ engagement ( Masry-Herzallh and Stavissky, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Often, difficulties and problems associated with modern technology come from downloading errors, issues with installation, login problems, problems with audio and video, etc. Previous research has shown that some features like file sharing, whiteboards, and annotation are not easy to use, resulting in the underutilization of conferencing functions ( Ming et al, 2021 ). In asynchronous learning environments, learning content cannot be provided in the same format as in offline classes, that is, it is impossible to provide real-time feedback and responses ( Littlefield, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation